The conservation of southern African terrestrial ecosystems, with special reference to the role of fire and the control of invasive alien plants - Van Wilgen B. W. (Brian William) (Stellenbosch : Stellenbosch University, 2012)
Thesis (DSc)--Stellenbosch University, 2008.